TINGKAT KEPATUHAN PENGOBATAN DAN PERUBAHAN GAYA HIDUP SEHAT, PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS TEGALLALANG I, BALI TAHUN 2014 - Andrew Valentinus Purwanto; Ayu Kartika Sari (DiscoverSys Inc., 2016)
Hypertension is one of the factor that cause heart disease, stroke, and death. Based on Riskesdas 2013, there were 25,8% people â‰¥ 18 years old who suffered from hypertension in Indonesia and 19,9% in Bali. There were 620 cases of hypertension in Puskesmas Tegallalang I and became the first cause of death in 2013 in Puskesmas Tegallalang I. The purpose of this study to know the overview of medication compliance and lifestyle modification in hypertensive patient in working area of Puskesmas Tegallalang I. This study is using descriptive cross sectional model. Datas were obtained by interview using a questionnaire to 41 sample. Based on the result of analysis, 87,8% have low compliance, 12,2% have medium compliance, and no one has high compliance. The result also shows 39% people decreased in consumption of tobaco, 4,9% decreased in consumption of alcohol, 36,6% decreased in consumption of coffee, 4,9% decreased in duration of watching television, 31,7% increase the frequency of sport in a week, and 34,1% increased in duration of sport. Most of the subject of this study have a low medication compliance.Â